MARIVAUX-PLAYWRIGHT AND A GERMAN THEATRE OF THE 18th CENTURY - Natalia T. Pakhsaryan (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article deals with the problem of the influence of the French Marivaux Theatre on the development of German drama in the 18th century. The relevance of this problem is determined, firstly, by the insufficiency of the study of Marivaux’s creative work in the national literature science, which considerably limits the ideas about the process of development of dramaturgy in France and about the evolution of the genre of the French national comedy in particular. Secondly, due to the lack of thoroughness of the Marivaux Theatre’s understanding, the question of the ways of the formation and development of the German theatre of the 18th century, its relations with the French dramaturgy, which partly determined the prospects of the expansion of the German dramaturgy, remains not fully elucidated. In Western European literary criticism, the problem of the internal connection between Marivaux’s comedies and the German theater had already become acute in the 1970s. In Russian science, however, Marivaux’s dramaturgical experience was considered mainly in line with the peculiarities of European classical comedy, and the experience of studying the peculiarities of the German theater of the 18th century was limited to the aspect of polemics with French classicism. In this respect, attention was paid to the evolution of German drama from the imitation stage (Gottsched’s works) to the creation of the national German theatre in the works of reformer Lessing. Gottsched’s interest in the traditions of French theatre and his focus on the experience of Racine, Moliere, Deschamps, Destouches and others is already evident at the imitation stage. The experience of the Italian Marivaux’s comedy, with Harlequin as the main character, was perceived with restraint due to outdated ideas about Harlequin as a buffoon character. The article demonstrates how these performances were disproved by German translator of Marivaux’s comedy J.C. Krüger, who accentuates the sentimental and rocaille dominant in the image of Harlequin. The article focuses on the influence of Marivaux’s comedies on the evolution of comic poetics in Lessing’s playwrights, which manifested itself 1) in the reduction of the role of male characters and the promotion of female heroines, 2) exclusion farcical beginning from the comedy, 3) in the balance of comic situations and comic in words, which led to an increase in the role of such a laughing technique as quiproquo. This evolution seems to indicate that Lessing had mastered the literary experience of Rococo. Such an approach to the study of the specifics of the development of the German theater of the 18th century makes it possible to go beyond the usual framework of the notion of confrontation between the German drama of the French theatrical tradition, which is identified only with Classicism, and to describe more precisely the interaction of Rococo and Sentimentalism, as well as Rocaille and Sentimental poetics with the ideas of Enlightenment.